Study the Glucose Transport, Angiogenesis and Apoptosis Behavioral through Chemotherapy Treatment According to Receptors Status in Women with Breast Cancer - Hamzah H. Kzar1 , Moshtak A. wtwt2 , Moaed E. Al-Gazally3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Glucose transporting into cells, angiogenesis, and apoptosis are the main factors that inducing the progression of many types of cancers including breast cancer. BC progression was seen as a multi-step process involving progressive changes from normal to hyperplasia with and without atypia, carcinoma in situ, invasive carcinoma, and metastasis. Aim: Assessment the role of glucose transport-1 (GLUT-1), vascular endothelial growth factor (VEGF), and cluster of differentiation factor(CD44) as a glucose transporting into cells, angiogenesis, and apoptotic factors in women with BC whom receiving chemotherapy. Method and Subjects: 120 women with BC included in this study as a patients group as well as 120 apparently healthy women as control. The women with BC is divided into sub-groups depending on chemotherapy treatment status. GLUT-1, VEGF, and CD44 were investigated by ELISA method. Results: This study suggested that highly significant differences in the mean and standard division of GLUT?1 and VEGF in all cases of women with BC compare to control group (P-Value< 0.05). The levels of GLUT?1 was highly significant difference between two subgroup have Her?2 positive and negative (p < 0.001), and the levels of VEGF, and CD44 in patients subgroups were significant (p< 0.05). Conclusion: The following up of the progression and responding to chemotherapy treatment may be more easy by estimation the glucose transporting, angiogenesis, and apoptotic markers in women with BC.